Elaboración de un suplemento nutricional a base de semillas de guanábana (Annona muricata) y quinua (Chenopodium quinoa). - Barragán Plúas, Sindy Narcisa (2024)
The present study on the development of a nutritional supplement based on soursop seeds (Annona muricata) and quinoa (Chenopodium quinoa) was carried out through an experimental study applying quantitative and bibliographic research where the development of 3 treatments was proposed. of the supplement and to obtain the best treatment, we worked with a group of 30 people where the results indicated that treatment 1 presented the greatest acceptability in the parameters of color, smell, flavor and texture where the physical and chemical characteristics of the treatment were subsequently evaluated. . 1 recording in quinoa seeds a humidity of 8.94% with 2.32% ash in addition to 7% fat, 6.23% fiber and 12.93% protein. On the other hand, soursop seeds presented 4.51% humidity of 4.51% with 1.62% ash in addition to 17.43% fat, 26.56% fiber and 14.66% protein. On the other hand, in the mixture, the humidity remained the same as in quinoa with 8.94%, while the other nutritional characteristics were a combination of both ingredients, registering 2.15% ash with 22.28% fat, in addition to 27.4% fiber and 25.26% protein, likewise. Regarding the microbiological parameters, the supplement showed safety in its results. Based on the analysis of the results, it was concluded that quinoa provides a notable amount of protein and a moderate amount of fat and fiber, soursop seeds stand out for their high fat and fiber content, although with a lower amount of protein. The mixture combined these characteristics, offering a nutritional balance and being beneficial for the formulation of food supplements.